An Acute Case of Herpes Zoster Ophthalmicus with Ophthalmoplegia - Wasim Hakim; Rosalie Sherman; Tamer Rezk; Kanwar Pannu (Case Reports in Ophthalmological Medicine, 2012)
Herpes zoster ophthalmicus (HZO) with oculomotor nerve involvement is rare, even rarer as an acute presentation rather than sequelae of HZO. In this paper we present a case of cutaneous HZO in which our patient's initial presentation was one of complete ophthalmoplegia.